Black mother educators : advancing praxis for access, equity and achievement - Jackson, Tambra O. (Contemporary perspectives on access, equity, and achievement., 2021)
"Drawing upon the theoretical frameworks of Beauboeuf-Lafontant (2002), Collins (2009), Crenshaw (1991), and Dillard (2012), this volume makes a case for centering the voices and experiences of Black women in the protection and educational uplift of Black children. While examinations of how Black educators articulate and enact a need to protect Black students from racialized harm exist (McKinney de Royston et. al., 2020), this book is a collection of autoethnographic narratives from Black mother educators who work at the intersections of their personal and professional identities to protect Black children. Intersectionality allows us to look at the nexus of our identities in regards to race, gender and occupation-- as Black, women and educators. Our goal for this volume was to bring together scholars who can support theorizing the intersectionality of our identities as Black mothers and educators, particularly its influence on our pedagogical practices and the safekeeping of Black children. This volume explicates stories of motherwork from Black mother educators whose professional spaces span K-12 to higher education contexts. Collectivity, this volume expounds upon the dimension of "protector" within the literature on Black women teachers"--